La civilización pocha en México - Julio de la Fuente (Estudios sobre las Culturas Contemporáneas)
An interesting work that reflects upon the different levels in which the United States society intervene in the Mexican one. The author makes refference to a detailled and complete description about the significance and importance of the mass media, radio, tv. Ition to democracy was a route guided by news media and supported by the professional communic.